Intramyocardial transplantation of mesenchymal stromal cells for chronic myocardial ischemia and impaired left ventricular function: Results of the MESAMI 1 pilot trial. (15th April 2016) - Guijarro, D.; Lebrin, M.; Lairez, O.; Bourin, P.; Piriou, N.; Pozzo, J.; Lande, G.; Berry, M.; Le Tourneau, T.; Cussac, D.; Sensebe, L.; Gross, F.; et al.
Abstract: Background: The MESAMI 1 trial was a bicentric pilot study designed to test the feasibility and safety of intramyocardially injected autologous bone marrow-derived mesenchymal stromal cells (MSCs) for the treatment of ischemic cardiomyopathy. Methods and results: The study included 10 patients with chronic myocardial ischemia, left ventricular (LV) ejection fractions (EFs) of ≤ 35%, and reversible perfusion defects who were on stable optimal medical therapy and were not candidates for revascularization. MSCs (mean: 61.5 × 10 6 cells per patient) were injected into 10–16 viable sites at the border of the LV scar via a NOGA-guided catheter. Both primary endpoints, feasibility (successful harvest, expansion, and injection of autologous MSCs) and safety (absence of severe adverse events [SAEs]) were met in all 10 patients at the 1-month follow-up time point, and none of the SAEs reported during the full 2-year follow-up period were attributable to the study intervention. The results of secondary efficacy endpoint analyses identified significant improvements from baseline to Month 12 in LVEF (29.4 ± 2.0% versus 35.7 ± 2.5%; p = 0.003), LV end-systolic volume (167.8 ± 18.8 mL versus 156.1 ± 28.6 mL; p = 0.04), 6-min walk test and NYHA functional class. Conclusions: Our results suggest that autologous MSCs can be safely administered to the hearts of patients with severe, chronic, reversible myocardial ischemia and impaired cardiac function and may be associated with improvements in cardiac performance, LV remodeling, and patient functional status. A randomized, double blind, multicenter, placebo-controlled clinical trial (MESAMI 2) will evaluate the efficacy of this treatment approach in a larger patient population. Clinical Trial Registration: Unique identifier: NCT01076920.